2015
DOI: 10.1016/j.amjmed.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Treatment-resistant Hypertension Among Individuals with History of Stroke or Transient Ischemic Attack

Abstract: Background and Purpose Blood pressure control is a paramount goal in secondary stroke prevention; however, high prevalence of uncontrolled blood pressure and use of multiple antihypertensive medication classes in stroke patients suggest this goal is not being met. We determined the prevalence and factors associated with apparent treatment-resistant hypertension in persons with/without stroke or transient ischemic attack.. Methods Data came from REGARDS, a national, population-based cohort of 30,239 black and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…Another contributing factor is that many patients with hypertension are under-treated. A recent study showed that hypertension treatment after vascular events may be inadequate, and another study showed high rates of apparent treatment-resistant hypertension in TIA and stroke patients [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Another contributing factor is that many patients with hypertension are under-treated. A recent study showed that hypertension treatment after vascular events may be inadequate, and another study showed high rates of apparent treatment-resistant hypertension in TIA and stroke patients [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…17, 19, 20 In REGARDS, SBP and DBP were measured twice, 30 seconds apart, using an aneroid sphygmomanometer (American Diagnostic Corporation, Hauppauge, NY) after the participant had been seated for 5 minutes. 18, 20, 21 These measurements were averaged for analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…17, 19, 20 In REGARDS, SBP and DBP were measured twice, 30 seconds apart, using an aneroid sphygmomanometer (American Diagnostic Corporation, Hauppauge, NY) after the participant had been seated for 5 minutes. 18, 20, 21 These measurements were averaged for analysis. In MESA, SBP and DBP were measured three times at 2 minute intervals using a Dinamap model Pro 100 automated oscillometric sphygmomanometer (GE Medical Systems Information Technologies, Inc., Milwaukee, Wisconsin) after participants rested for 5 minutes in a seated position.…”
Section: Data Collectionmentioning
confidence: 99%
“…17,18 In persons with HTN, the prevalence of AF has been reported to be higher among those with uncontrolled HTN compared to controlled HTN. 8 Antihypertensive medications such as beta-blockers and angiotensin converting enzyme inhibitors (ACE-I) are associated with decreased AF risk.…”
Section: Introductionmentioning
confidence: 99%